PERANCANGAN NENGGALA DISK DUPLICATOR (NDD) UNTUK MENDUKUNG PROSES INVESTIGASI FORENSIK DIGITAL - Fietyata Yudha (Teknoin, 2018)
The development of information technology simplify human life. Its evoke crime loopholes, cyber crime. When solving criminal cases that utilize information technology is required the digital forensic science. In carrying out a digital investigation known multiple frameworks around the worlds. Every devices, every organization has their own framework. The most common framework divided into 4 sections. Preservation, Acquisition, Analysis, and Reporting are the most common used around the worlds. Acquisition is a key part of the investigation process because in this process digital evidence is collected form the electronic evidence. The acquisition processes uses special equipment. Forensic acquisition equipment mostly made by forensic vendors in the world. The problems that arise in the academic realm is the price of the equipment is quite expensive. The existence of the above problem there is a gap to conduct research on the applied field of development of tools for forensic acquisition. This study provides an early overview of the design of a digital forensics acquisition tool called Nenggala Disk Duplicator.